In vitro antioxidant and antimicrobial potential of Sterculia urens Roxb. root extract and its bioactive phytoconstituents evaluation - Anjali Shukla; Krishna Desai; Nainesh Modi (SpringerOpen, 2020)
Abstract Background The plant Sterculia urens Roxb. of Malvaceae family is comparatively understudied. Genus Sterculia is widely recognized by its phytomedicinal and ethnomedicinal attributes. The study is aimed to evaluate the qualitative analysis, Fourier transform infrared (FT-IR), thin layer chromatography (TLC), total phenolic content (TPC), antioxidant and antimicrobial activities of the crude hydro-methanolic extract of S. urens root. Results The antioxidant activity, antimicrobial assay for clinical isolates, and TPC were measured by DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging activity, agar well diffusion method, and Folin-Ciocalteu assay respectively. Hydro-methanolic extract confirmed the presence of alkaloids, flavonoids, tannins, phenols, saponins, steroids, and glycosides as primary and secondary metabolites, which was later confirmed by TLC. FT-IR spectroscopy revealed the presence of alkanes, alkenes, alkyl halides, halogen compounds, primary alcohol, tertiary alcohol, aldehyde, aromatic amine, secondary amines, amide group, and carboxylic acid. The crude extract was composed of a significant quantity of total phenolic content with 705 ± 0.40 mg GAE/g. Synergistically, the IC50 value of the crude extract and ascorbic acid was found to be 27.055 μg/ml and 37.244 μg/ml, respectively, which suggests that root extract possesses strong antioxidant properties. The majority of the microbial strains exhibited varying degrees of sensitivity to the root extract with a notable inhibitory effect against Escherichia coli, Klebsiella pneumoniae, and Penicillium glaucum. Conclusion The findings of this analysis suggest that the hydro-methanolic extract from S. urens root exhibit antioxidant activity quantified by its ability to scavenge DPPH; antimicrobial activity displayed appreciable microbial sensitivity. These properties are associated with the presence of high phenolic content, different secondary metabolites, and their functional groups. The results are suggestive that S. urens root is rich in bioactive compounds, which serve as a novel natural source for potential therapeutic applications. Graphical abstract